Rodenticide poisoning in children: A study of clinical profile and electrocardiographic changes - Sugunan, Sheeja; Krishnan, Rekha; Kumar, K K Santhosh; Geetha, S (Indian Journal of Child Health, 2022)
Objectives: To study the clinical profile and electrocardiographic (ECG) changes in rodenticide poisoning in children. Methods: Patients admitted with a history of ingestion of rat poison between October 2014 and October 2016 were included in the study. Clinical history was taken in detail, and stomach wash samples were sent for toxicological analysis. Continuous ECG monitoring was done in all cases. Investigations to assess organ functions and coagulation profile were done at admission and repeated as indicated. Results: There were 17 cases of rodenticide poisoning. Zinc phosphide was the rodenticide identified in 50% of cases, bromodiolone in 30%, and yellow phosphorous in 20% cases. Only 23% presented within 1 h of ingestion and only 12% received stomach wash from referring hospital. Out of the 17 cases, 12 cases (70%) were symptomatic, of which 42% hadminor symptoms such as vomiting and abdominal pain and 58% had major symptoms including dysrhythmias, shock, coagulation abnormality, hepatic failure, and seizures. ECG changes were observed in 7 cases (42%), and coagulopathy was seen in 2 (12%) cases of which one had hepatic failure. The mean time of onset of ECG changes was 19.7 h (range 9-36 h). The overall mortality rate was 17.6%. Cardiac arrhythmia was the most common cause of death (66%). Conclusion: Zinc phosphide has been detected as the most common chemical being used as domestic rodenticide. Transient rate abnormalities, metabolic acidosis, fever, and leukocytosis are early markers of toxicity and they should be looked for in all cases. General public, medical, and aramedicalpersonnel should be made aware of the toxic nature of rodenticides.